Balanced hierarchical method of collision detection in virtual environment - Sulaiman, Hamzah Asyrani; Bade, Abdullah (Springer, 2011, 2011)
Determine the successful configuration between rigid bodies that come into contact is always a fundamental problem in computer visualization problem. Given the simulation that needs to maintain the speed of intersection, it is not always fast enough to compute the complete iteration between moving polyhedral. In this paper, we introduced a splitting algorithm that is able to successfully divide the hierarchical construction in virtual environment. By enhancing the capabilities of splitting rules of Bounding-Volume Hierarchies (BVH), the construction of BVH is improved and is able to provide fast collision detection method between two successive configurations.